Differential response of esophageal cancer cells to particle irradiation - Sarah Hartfiel; Matthias Häfner; Ramon Lopez Perez; Alexander Rühle; Thuy Trinh; Jürgen Debus; Peter E. Huber; Nils H. Nicolay (Radiation Oncology, 2019)
Abstract Background Radiation therapy is a mainstay in the treatment of esophageal cancer (EC) patients, and photon radiotherapy has proved beneficial both in the neoadjuvant and the definitive setting. However, regarding the still poor prognosis of many EC patients, particle radiation employing a higher biological effectiveness may help to further improve patient outcomes. However, the influence of clinically available particle radiation on EC cells remains largely unknown. Methods Patient-derived esophageal adenocarcinoma and squamous cell cancer lines were treated with photon and particle irradiation using clinically available proton (1H), carbon (12C) or oxygen (16O) beams at the Heidelberg Ion Therapy Center. Histology-dependent clonogenic survival was calculated for increasing physical radiation doses, and resulting relative biological effectiveness (RBE) was calculated for each radiation modality. Cell cycle effects caused by photon and particle radiation were assessed, and radiation-induced apoptosis was measured in adenocarcinoma and squamous cell EC samples by activated caspase-3 and sub-G1 populations. Repair kinetics of DNA double strand breaks induced by photon and particle radiation were investigated. Results While both adenocarcinoma EC cell lines demonstrated increasing sensitivities for 1H, 12C and 16O radiation, the two squamous cell carcinoma lines exhibited a more heterogeneous response to photon and particle treatment; average RBE values were calculated as 1.15 for 1H, 2.3 for 12C and 2.5 for 16O irradiation. After particle irradiation, squamous cell EC samples reacted with an increased and prolonged block in G2 phase of the cell cycle compared to adenocarcinoma cells. Particle radiation resulted in an incomplete repair of radiation-induced DNA double strand breaks in both adenocarcinoma and squamous cell carcinoma samples, with the levels of initial strand break induction correlating well with the individual cellular survival after photon and particle radiation. Similarly, EC samples demonstrated heterogeneous levels of radiation-induced apoptosis that also corresponded to the observed cellular survival of individual cell lines. Conclusions Esophageal cancer cells exhibit differential responses to irradiation with photons and 1H, 12C and 16O particles that were independent of tumor histology. Therefore, yet unknown molecular markers beyond histology may help to establish which esophageal cancer patients benefit from the biological effects of particle treatment.